Pengaruh Profitabilitas, Likuiditas, Dan Leverage Terhadap Financial Distress Perusahaan Sektor Energi Di Bei 2020–2024: The Effect Of Profitability, Liquidity, And Leverage On Financial Distress Among Energy Sector Companies On The Idx, 2020–2024 - Mu'alfad Zulfikar Purwanto; Axel Giovanni; Shinta Ratnawati (Universitas Bojonegoro, 2026)
This study examines the impact of profitability, liquidity, and leverage on financial distress in IDX-listed energy companies from 2020-2024. Using logistic regression on 105 observations, the results indicate that profitability significantly reduces financial distress, whereas liquidity and leverage have no significant effect. Consequently, management should prioritize operational efficiency to sustain profitability, as adequately managed debt and liquidity do not trigger crises.